What explains India's poor performance in garments exports: Evidence from five clusters? - Saon Ray (Indian Council for Research on International Economic Relations (ICRIER), 2019)
In this paper, we examine the Indian apparel industry to examine the effect of clusters on the sales of this industry. The data has been collected through a primary survey in five garments clusters in India. The variable that is significant in explaining sales in most equations is technology proxied by imported machinery. It has been argued that inter-firm linkages and linkages between firms, service providers and institutions are crucial for competitiveness and this is best achieved through a cluster. Studies on clusters have shown that some clusters have been able to deepen their inter-firm division of labour, raise their competitiveness and break into international markets. Agglomeration may arise from the specialization of a region in a particular industry where firms share common inputs or knowledge. We argue that the main reason for India's poor performance in garments (compared to other South Asian countries such as Bangladesh) is the lack of proper clusters. The development of the cluster in India has followed the "top down" approach and the natural process through which linkages are developed are yet to occur in most clusters.
Keywords: F14; L67; L23; 330; Competitiveness; garment; cluster; South Asia